MIS Express Based Passenger Flows Classification Aimed at Determination of Interregional Travel Behaviour in the Russian Federation - E. A. Makarova; K. V. Surzhin; A. G. Piunov; A. V. Sokolovskiy (Вестник Научно-исследовательского института железнодорожного транспорта)
The paper contains classification of passenger traffic flows with various levels of detail, covering those between the constituents of the Russian Federation (inclusive of specification by passenger car types) and between individual stations. Partition into classes was carried out employing ABC analysis. The authors give a description of the class extraction method and unpack it in the prac-tical context of railway passenger services. There is described methodological basis of the performed classification and passenger traffic volume calculations. Also presented is the classification algorithm developed within the framework of the discussed study. There is analyzed the structure of the extracted passenger flow classes for each level of detail. There are also compared traffic volumes shares of individual classes and numbers of passenger flow streams in these classes. Justification is presented of existing trends stable character as related to passenger flows partition into classes with use of historical data.